Epidemiology of chronic myeloid leukemia - Hellmann, Andrzej; Maciej Zaucha, Jan; Stachera-Grzenkowicz, Małgorzata; Prejzner, Witold; Homenda, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2004)
This article presented the epidemiological data of the patients with diagnosed chronic myeloid leukemia in 1993–2002. The patients lived in the Pomorskie province. 164 patients (64 women and 100 men) with chronic myeloid leukemia treated at the Department of Hematology of the Gdańsk Medial University, hematology outpatients departments and city hospitals in the Pomorskie province were analyzed. The overall age standardized incidence rate for chronic myeloid leukemia in the Pomorskie province is 0.9/100 000 per year. The age standardized rate is higher for males (1.1/100 000 per year) to females (0.7/100 000 per year). There is a preponderance of males and the sex ratio of males to females is 1.9:1. The highest incidence rate for males was observed in the age group of more than 60 years with the value of 3.21/100 000 per year. The highest incidence rate for females was also observed in the age group of more than 60 years. The overall prevalence rates for chronic myeloid leukemia in 2002 were 4.0/100 000 persons. The highest mortality rate (1.59/100 000 persons) was observed in the oldest reported group (>60 years). The highest number of diagnosed patients with CML was in 2001: 25 cases, the fewest patients: in 1993 and 2000 – 10 cases. The median age at the diagnosis was 52 years, the older population was that of females (median age of 55 years), the younger population was that of males (median age of 50 years). At the time of diagnosis the most patients were in the chronic phase (89.7%). According to the data, the estimated number of patients with CML in Poland is 1 400.